2020
DOI: 10.1108/ijph-03-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

Multiple burdens of stigma for prisoners participating in opioid antagonist treatment (OAT) programmes in Indonesian prisons: a qualitative study

Abstract: Purpose In spite of the effectiveness of opioid antagonist treatment (OAT) in reducing injecting drug use and needle sharing, programmes in prison continue to be largely stigmatised. This affects programme participation and the quality of programmes delivered. This study aims to explore how Indonesian prison staff and prisoners perceived and experienced stigma relating to prison OAT programmes and identify potential strategies to alleviate this stigma. Design/methodology/approach Three prisons in Indonesia w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…In common with other studies (Sto ¨ver and Kastelic, 2016; Komalasari et al, 2020;Komalasari et al, 2021), this study found considerable misunderstandings relating to the use of methadone programmes as part of an HIV harm reduction strategy amongst both prison staff and prisoners and across all three study prisons. The idea that methadone is simply another type of illicit drug, was prevalent amongst most prison officers and some health-care staff, again across all three prisons.…”
Section: Discussionsupporting
confidence: 69%
“…In common with other studies (Sto ¨ver and Kastelic, 2016; Komalasari et al, 2020;Komalasari et al, 2021), this study found considerable misunderstandings relating to the use of methadone programmes as part of an HIV harm reduction strategy amongst both prison staff and prisoners and across all three study prisons. The idea that methadone is simply another type of illicit drug, was prevalent amongst most prison officers and some health-care staff, again across all three prisons.…”
Section: Discussionsupporting
confidence: 69%